PENERAPAN MODEL PEMBELAJARAN KOOPERATIF SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA POKOK BAHASAN TERMOKIMIA DI KELAS XI MIA SMA NEGERI 1 TANJUNGPINANG - ', Aisyah; Copriady, Jimmi; Amran, Elva Yasmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research aimed to improve the achievement of learners on termochemistry subject in XI MIA class SMAN 1 Tanjungpinang. This research was a kind of experimental research with pretest-posttest design. The research was conducted in SMAN 1 Tanjungpinang the samples of the research were the students of XI MIA1 class as the experimental class and students of XI MIA2 class as the control class which were determined randomly after doing normality test and the homogeneity test. The learning process of experimental class and control class used scientific approach which was based on the curriculum in 2013. Experimental class was a class which was given the treatment that used cooperative learning model snowball throwing while the control class was not. Based on the result of data analysis test, we obtained tcount ttabel 4,27 1,67. It meant that the use of cooperative learning model snowball throwing could improve students learning achievement on termochemistry subject in XI MIA class SMAN 1 Tanjungpinang.Key Words : Snowball Throwing , Learning Outcomes, Termochemitry